O espaço dos possíveis, de Pierre Bourdieu - Maria Thereza Rosa Ribeiro (Ciências Sociais Unisinos)
We analyze the approach from the point of view of the place of agents in “The Misery of the World,” by Bourdieu et al., where the authors seek to understand the representation of agents classified as having negative symbolic capital. On the basis of the emergence of the voices of the agents, Bourdieu observes the space of the possible, but impossible to overcome the conflicts implicit in the different visions and in the confrontation of those who experience the condition of discrimination. Understanding the universe of agents who live in poverty is seen in the key of the reflexivity of practice that flaking doxa through the hermeneutics of stigmatized identities. In the reference of participant objectification, the interface between phenomenology and “Pascalian meditations” is opposed to positivism and scientific rationalism.